FACTORS THAT INFLUENCE THE TURNOVER OF EMPLOYESS IN TOURISM SECTOR IN BULGARIA - Vitanova, Valeria (Horizons - International Scientific Journal, 2020)
Staff turnover is a problem that is distinguished by great importance and growing relevance to business practice worldwide. Its importance is directly related to the negative effects it has on the organization dynamic and effectiveness. The main purpose of the paper is to find out and summarize the basic factors that have influence on the employee’s decision to leave the company they work for in the tourism sector in Bulgaria. The relevance of the selected topic is confirmed by many challenges specific to field of tourism. The low-skilled manpower and weak motivation, which in some cases is even lacking are only a few of the well- known challenges that tourism enterprises face in their effort to survive in the Bulgarian market and achieve their goals. Human capital is the key for the success so it is of critical importance to go in depth and analyze factorsthe determine the decision of employees to leave the company in order to work on a strategies to prevent the lost especially of well trained and productive organizational members.